"I Know a Guy and He's Got Guns Galore": Accessing Crime Guns in the Australian Illicit Firearms Market. Issue 5 (4th May 2023) - Bright, David; Halsey, Mark; Goldsmith, Andrew; Goudie, Sharyn
ABSTRACT: Despite there being a highly regulated firearms market, Australian criminals continue to have significant access to illicit firearms. This paper focuses specifically on the role of brokers in the illicit firearms market. It draws from 75 in-depth interviews with prisoners convicted of serious gun-related crimes in Australia. We note how these actors occupy the margins of our interview data yet are seemingly central to the supply and circulation of firearms. Six main means of illicit firearm acquisition are identified, ranging from supply through family members to being vouched for by a known person who provides a bridge to the appropriate supplier (or 'guy'). The role of straw purchasers, theft, and/or manufacturing in the illicit firearm trade are also explored. We conclude with a provisional profile of the 'middleman' and comment on the resilience of the underworld code and its protection of key actors in gun crime milieux as well as implications for prevention and law enforcement.